2013
DOI: 10.1002/cjce.21824
|View full text |Cite
|
Sign up to set email alerts
|

A dual approach for modelling and optimisation of industrial urea reactor: Smart technique and grey box model

Abstract: Urea has the highest demand among all solid nitrogenous fertilisers within the agriculture industry. In this paper, a mathematical model and an Artificial Neural Network (ANN) technique are proposed for the simulation and optimisation of the urea plant in an industrial petrochemical company. The developed mathematical model consists of complex vapour–liquid equilibria for the NH3–CO2–H2O–(NH2)2CO system in thermodynamic and reaction frameworks. The smart technique (e.g. ANN) considers the CO2 conversion in ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 27 publications
(109 reference statements)
0
17
0
Order By: Relevance
“…Further information about ANN can be found in the recent literature [36][37][38][39][40][41][42][43][44][45][46][47].…”
Section: Artificial Neural Networkmentioning
confidence: 99%
“…Further information about ANN can be found in the recent literature [36][37][38][39][40][41][42][43][44][45][46][47].…”
Section: Artificial Neural Networkmentioning
confidence: 99%
“…There are a number of reported studies ( [2]; [3]; [4]; [5]; [6]; [7]; [8]; [9]; [10]; [11] and [12]) on mathematical modeling and/or simulation synthesis section -the reaction section. Nevertheless, there is still a range of restrictions for simulating such a complex process.…”
Section: Introductionmentioning
confidence: 99%
“…Deviations from industrial data were reported as less than 5.0% for liquid composition in the reactor outlet. Zendehboudi et al (2014) proposed a mathematical model for urea reactor based in a UNIQUAC approach. When compared to industrial data, deviation less than 2.3% for the liquid outlet stream is obtained.…”
Section: Introductionmentioning
confidence: 99%
“…ANN fits any complex nonlinear functions, given sufficient complexity of the trained network . ANN has been applied successfully to many areas in chemical engineering, such as cracking furnace modelling and optimization, optimization of CO 2 capture cost using ANN surrogate models, optimization of industrial urea reactors, frictional pressure drop of tapered bubble columns, and estimation of gas‐oil minimum miscibility pressure using PSO‐ANN …”
Section: Introductionmentioning
confidence: 99%
“…ANN fits any complex nonlinear functions, given sufficient complexity of the trained network. [15] ANN has been applied successfully to many areas in chemical engineering, such as cracking furnace modelling and optimization, [16][17][18][19] optimization of CO 2 capture cost using ANN surrogate models, [20,21] optimization of industrial urea reactors, [22] frictional pressure drop of tapered bubble columns, [23] and estimation of gas-oil minimum miscibility pressure using PSO-ANN. [24] Although ANN has powerful function approximation ability, clear mathematical expression, and easy availability of implementation for training and analysis, the success of its application usually depends on structure selection and distribution of training data.…”
Section: Introductionmentioning
confidence: 99%